Controlling catheter-related bloodstream infections through a multi-centre educational programme for intensive care units. Issue 3 (November 2017) - Musu, M.; Finco, G.; Mura, P.; Landoni, G.; Piazza, M.F.; Messina, M.; Tidore, M.; Mucci, M.; Campagna, M.; Galletta, M.
Summary: Background: Bloodstream infections (BSIs) associated with insertion and maintenance of central venous catheters (CRBSIs) are the most frequent causes of healthcare-associated infections in intensive care units (ICUs). They are responsible for increased length of hospital stay and additional healthcare costs. Aim: To investigate whether an educational programme aimed at healthcare workers resulted in a significant change in the level and trend of infections. Methods: The research was conducted in five Italian ICUs from July 2012 to August 2014. Surveillance and educational interventions to control infections were applied. Compliance with hand hygiene procedures was assessed via relative risk and 95% confidence interval. Interrupted time-series analysis was used to investigate the change in level and trend of infection during the intervention. Findings: Compliance with hand hygiene procedures improved during the intervention for all staff groups, but physicians showed the lowest compliance rates (nurses from 52.4% to 92.1%; nurse aides from 71.0% to 92%; physicians from 71.0% to 92%; P < 0.001). Significant reductions of 21–55% in CRBSI were observed during the intervention. Small improvements in the monthly infection trend were also observed, but these were not statistically significant. Conclusion: An educational programme focusing on general good infection control practice, rather than CVC care bundles, led to a decreased CRBSI rate, even if the improvement was not sustained over time. Continuous performance feedback should be provided to promote long-term adherence to guidelines among all health workers.